Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
\(x\left(x+4\right)\left(x+6\right)\left(x+10\right)+128\)
\(=x\left(x+10\right)\left(x+4\right)\left(x+6\right)+128\)
\(=\left(x^2+10x\right)\left(x^2+10x+24\right)+128\)(1)
Đặt \(x^2+10x=t\)
\(\Rightarrow\left(1\right)=t\left(t+24\right)+128=t^2+24t+128\)
\(=t^2+8t+16t+128\)
\(=t\left(t+8\right)+16\left(t+8\right)\)
\(=\left(t+8\right)\left(t+16\right)\)(2)
Mà \(x^2+10x=t\)(theo cách đặt) nên \(\left(2\right)=\left(x^2+10x+8\right)\left(x^2+10x+16\right)\)
\(x^3+2x-3\)
\(\Rightarrow x^3+6x-4x-3\)
\(\Rightarrow\left(x^3-4x\right)+\left(6x-3\right)\)
\(\Rightarrow x\left(x^2-4\right)+3\left(x-2\right)\)
\(\Rightarrow x\left[\left(x+2\right)\left(x-2\right)\right]+3\left(x-2\right)\)
\(\Rightarrow\left(x-2\right),\left[x\left(x+2\right)+3\right]\)
\(1,x\left(x+4\right)\left(x+6\right)\left(x+10\right)+128\\ =\left(x^2+10x\right)\left(x^2+10x+24\right)+128\\ =\left(x^2+10x+12-12\right)\left(x^2+10x+12+12\right)+128\\ =\left(x^2+10x+12\right)-12^2+128=\left(x^2+10x+12\right)^2-16\\ =\left(x^2+10x+12-16\right)\left(x^2+10x+12+16\right)\\ =\left(x^2+10-4\right)\left(x^2+10x+28\right)\)